Face Recognition & AI Based Smart Attendance Monitoring System - Hati, Ankur; Saha, Sagar; Mandal, Ankita; Saha, Preeti; Sahana, Sudipta; Singh, Dharampal (International Journal of Computer Sciences and Engineering, 2021)
In today’s generation, authentication is one of the biggest problems in our society. So, one of the most known techniques used for authentication is human face recognition, which is also known as HFR. For example- nowadays we can unlock our phone using the face recognition feature. In the existing system, Our lecturers take attendance manually which is somewhat time-consuming and old school type. So, our Artificial Intelligence-based attendance monitoring system will be capturing the faces of every student in a class during attendance and the result will get stored in the database automatically. There will be no extra Radio frequency Identification card, people need to carry anymore and this system will be the most authentic system of taking attendance. The system stores the faces that are detected and automatically uploads the attendance to the database. Using This process our primary goal is to help lecturers as well as students to track and manage student's attendance and absenteeism.